Migration in Myanmar - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2024)
Key Findings • Over 1.5 years (between December 2021 and June 2023) at least 18.5 percent of the population or more than 10 million people migrated: 6.5 million individuals 15 years and older left their households and 3.1 million individuals moved together as a household or family unit. • Fifty six percent of individuals who migrated cited employment as at least one of their drivers for migration. • More men left their households to migrate than women. Most individuals migrated for work within Myanmar, though over time more individuals departed to find work abroad. • In the first half of 2023, 16 percent of households received remittances from at least one member who was residing overseas or in a different state or region. • Remittances contributed more to the household income of rural residents and the poor and were mostly used towards food purchases. Households receiving remittances had better dietary quality and were less likely to be poor. Recommended Actions • Set up programs that facilitate access to credit to reduce the need for migrants or households to take out high-interest loans for migration. • Develop support programs for communities experiencing high out-migration to enhance individuals' awareness of the associated risks, processes, and job opportunities linked to migration. • Create centers in high in-migration areas to aid migrants by providing resources, legal assistance, sustenance, shelter, and community support. • Monitor migration and evaluate the impact of policy changes.